SWOT and Triangle Model Marketing Service Analysis for Marketing Strategy: Implementation Study at Pandan Arang Boyolali Hospital - Ika Sulistyaningrum Hapsari; Sutopo Patria Jati; Septo Pawelas Arso (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
The hospital is a place for providing health services. In an effort to maximize services, a marketing strategy is needed so that the continuity of the hospital continues to run well. The study was conducted at the Pandan Arang Hospital in Boyolali in the Gastroentero-hepatology (GEHC) sub-specialist service, examining the current marketing strategy using SWOT analysis and the triangle marketing model. This research is descriptive-analytic with a qualitative approach. The primary data collection techniques were in-depth interviews (direct interviews), FGDs and observations; while the secondary data is taken from a review of previous research studies that contain the SWOT and the marketing triangle model. Description of the results and discussions that have been carried out, Pandan Arang Boyolali hospital GEHC sub-specialist service, is in quadrant 1. Quadrant I means the hospital is in a favourable position based on the IE matrix, the hospital has many strengths in dealing with many opportunities from the results of the calculation of internal factors using the IFE and EFE matrices. Even though it is in quadrant 1, Pandan Arang Boyolali hospital services for GEHC must develop strategies in dealing with external and internal threats to obtain opportunities and overcome threats so that they will become a superior hospital. The development strategy carried out is called the Alternative Marketing Strategy which has 9 steps of development strategy. In addition, the development strategy is also carried out using the Triangle Model Marketing. The Triangle marketing model is carried out from the results of internal and external factors analysis.  Abstrak: Rumah sakit merupakan tempat untuk memberikan pelayanan kesehatan. Dalam upaya memaksimalkan pelayanan, diperlukan strategi pemasaran agar kelangsungan rumah sakit tetap berjalan dengan baik. Penelitian dilakukan di Rumah Sakit Pandan Arang Boyolali di sub spesialis Gastroentero-hepatology, mengkaji strategi pemasaran saat ini menggunakan analisis SWOT dan model pemasaran segitiga. Penelitian ini bersifat deskriptif-analitik dengan pendekatan kualitatif. Teknik pengumpulan data primer adalah wawancara mendalam (wawancara langsung), FGD dan observasi; sedangkan data sekunder diambil dari tinjauan studi penelitian sebelumnya yang berisi SWOT dan model segitiga pemasaran. Deskripsi hasil dan pembahasan yang telah dilakukan, pelayanan sub spesialis GEHC RS Pandan Arang Boyolali berada pada kuadran 1. Kuadran I artinya rumah sakit berada pada posisi yang menguntungkan berdasarkan matriks IE, rumah sakit memiliki banyak kekuatan dalam menangani dengan banyak peluang dari hasil perhitungan faktor internal menggunakan matriks IFE dan EFE. Meskipun berada di kuadran 1, pelayanan RS Pandan Arang Boyolali untuk GEHC harus mengembangkan strategi dalam menghadapi ancaman eksternal dan internal untuk mendapatkan peluang dan mengatasi ancaman sehingga menjadi rumah sakit yang unggul. Strategi pengembangan yang dilakukan disebut dengan Strategi Pemasaran Alternatif yang memiliki 9 langkah strategi pengembangan. Selain itu, strategi pengembangan juga dilakukan dengan menggunakan Triangle Model Marketing. Model pemasaran segitiga dilakukan dari hasil analisis faktor internal dan eksternal.